New Directions in Thin Film Nanophotonics - K. V., Sreekanth; ElKabbash, Mohamed; Caligiuri, Vincenzo; Singh, Ranjan; De Luca, Antonio; Strangi, Giuseppe; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2019)
This book highlights recent advances in thin-film photonics, particularly as building blocks of metamaterials and metasurfaces. Recent advances in nanophotonics has demonstrated remarkable control over the electromagnetic field by tailoring the optical properties of materials at the subwavelength scale which results in the emergence of metamaterials and metasurfaces. However, most of the proposed platforms require intense lithography which makes them of minor practical relevance. Stacked ultrathin-films of dielectrics, semi-conductors, and metals are introduced as an alternative platform that perform unique or similar functionalities. This book discusses the new era of thin film photonics and its potential applications in perfect and selective light absorption, structural coloring, biosensing, enhanced spontaneous emission, reconfigurable photonic devices and super lensing.
Perfect light absorption in thin and ultra-thin films and its applications -- Realization of point-of-darkness and extreme phase singularity using nanophotonic cavities -- Phase change material-based nanophotonic cavities for reconfigurable photonic device applications -- Subwavelength nanopatterning using thin metal films -- Dielectric singularities in hyperbolic metamaterials -- Resonant gain singularities in hyperbolic metamaterials -- Metal/photoemissive-blend hyperbolic metamaterials for controlling the topological transition -- Guided modes of hyperbolic metamaterial and their applications -- Graphene and topological insulator-based active THz hyperbolic metamaterials.
Keywords: Surfaces (Physics).; Telecommunication; Surfaces (Technology).; Thin films; Lasers; Microtechnology; Microelectromechanical systems; Biomaterials; Surface and Interface and Thin Film; Microwaves, RF Engineering and Optical Communications; Surfaces, Interfaces and Thin Film; Laser; Microsystems and MEMS; Biomaterials